Dimensi Kualitas Pelayanan terhadap Kepuasan Konsumen - Sulton Sholehuddin; Fahrurrozi Rahman (JMK (Jurnal Manajemen dan Kewirausahaan), 2020)
This study aims to analyze and determine the effect of the dimensions of service quality simultaneously and partially on customer satisfaction Khai Khai Thai Tea Malang. The population numbered 310 customers and fulfilled the criteria of the research sample (accindental sampling). The research method uses a survey method with a quantitative research approach with a sample of 75 respondents, the analytical tool used is SPSS 20. This study concludes that there is a simultaneous influence of the dimensions of service quality dimensions on consumer satisfaction Khai Khai Thai Tea Malang. Partially the dimension of service quality dimensions, namely responsibility and empathy, influences, but not significantly to the variable of customer satisfaction, Khai Khai Thai Tea, the center of Malang City. While tangibles, reliability and assurance variables have a significant effect on the quality of Khai Khai Thai Tea services in Malang.